Recycling Roof Tile Waste Material for Wall Cover Tiles - Mulyono, Ambar; Aryani, Silfia Mona; Lulut, Joko (UI Scholars Hub, 2013)
Prior research on roof tile waste treatment has attempted to find the appropriate technology to reuse old roof tile waste by create wall cladding materials from it. Through exploration and experimentation, a treatment method has been discovered to transform the tile fragments into artificial stone that resembles the shape of coral. This baked clay artificial stone material is then processed as a decorative element for vertical surfaces that are not load-bearing, such as on the interior and exterior walls of a building. Before applying the fragments as wall tiles, several steps must be taken: 1) Blunting, which changes the look of tile fragments using a machine created specifically to blunt the roof-tile fragment edges, 2) Closing the pores of the blunted fragments as a finishing step that can be done with a transparent coat or a solid color of paint, 3) Planting the transformed roof-tile fragments on a prepared tile body made of concrete. In this study, the second phase is done using the method of ceramics glazing at a temperature of 700 °C. The finishing step is the strength of this product because it produces a rich color artificial pebble.